Sobre o estado atual da dogmática do dolo - Ceolin, Guilherme Francisco (2015)
The subject of the present research is the concept of intention. The objective is to analyse the current state of the problem, i.e., which are the main order of questions to reason the discussions about the concept of intention, as well as to analyse solution proposals. Bibliographical review and analyses were the methods used in this study, with a diverse explanation and critical analyses of ideas about the referred proposals. The explanation is divided in two chapters. In the first chapter, the current state of the question of the concept of intention under the contemporaneous criminal dogmatic is analysed. First, it is verified the unfeasible of the ontological foundation of the concept of intention, as it is stated that intent is defined in the normative relation, and not ontological, and that, because of this, it shall be deducted in a coherent way from the Criminal Law foundations. Thereafter, it is investigated what is the legacy of ideas brought by the objective imputation theory in the sphere of imputation of intention, as it is stated that it comes to relegate the analyses of a subjective type to a second degree of imputation, to decrease the relevance of the subjective type, as well as to insert in the action disvalue an objective face. The second chapter is dedicated to the concepts of intention proposed by scholars in order to suit to the current state of the problem and fill the gaps opened by the departure of the ontological foundation. Topics of terminology are analysed, a panorama of positions is traced in respect to content, a performance capacity of these are compared. A position is assumed regarding some of these questions and, at the end, critics are classified in order to provide a general view of the theme. Some of the main conclusions of the research are: intention is defined in the normative relation, and not ontological; the concept of intention shall be suitable to the creation of risk and, therefore, shall have an objective aspect that can be configured on the domain over the creation of the riks; in intentional cases, analysis of dominion over the creation of risk shall use special author's knowledge; the debate about the concept of intent has fulcrum in different understandings about the ratio legis of punishment of intend; the discussions about intention are direct results from the discussions about the foundation model of the Criminal Law and of the comprehension of the derived responsibility.